Князі Глинські: рання історія роду - Келембет, С. (Сiверянський лiтопис, 2019)
У статті досліджується історія князів Глинських із середини XV до початку XVI ст.
в період діяльності двох поколінь роду – синів та онуків першого достовірно відомого
князя Глинського. За структурою робота складається з окремих біографічних нарисів,
що згруповані у три підрозділи – за трьома основними лініями роду Глинських. Обґрунтовується помилковість тези Ю. Вольфа, прийнятої і в сучасній історіографії, про те,
що путивльська (середня) лінія Глинських нібито була галуззю молодшої, смоленської
лінії. Князь Богдан Федорович Глинський у 1493 р. згадується як перший відомий очільник дніпровських (черкаських) козаків. Найвищі кар’єрні досягнення князів Глинських
до 1500 р. були пов'язані з Сіверською землею. Тут окремі члени роду займали урядові
посади намісників (стародубського, чернігівського та путивльського). The article explores the history of the family of princes Glynsky from the middle of the XV
to the turn of the 15th and 16th centuries, more precisely, during the period of activity of two
generations – the sons and grandsons of Prince Ivan Oleksandrovich (?), the first reliable representative
of the family. According to the structure, the work consists of separate biographical
essays, which are grouped into three subsections — along the three main lines of the Glynsky
family. These lines, according to the testimony of the Glynsky ancestry of the mid-16th century,
were founded by three sons of Prince Ivan — Boris, Fyodor and Semyon. However, at the end
of the XIX century. Y. Wolf, developing the Glynsky genealogy, recognized two junior lines,
Cherkasko-Putyvl’ska and Smolenska, as different branches of the same Cherkasko-Smolenska
line – descendants of Prince Semyon Ivanovich; prince Fedor, thus, «remained» childless. This
genealogical scheme, thanks to Wolf’s high prestige, was later firmly established in historiography,
being accepted in modern works. However, the study of sources showed that the evidence of the
ancient ancestry about the origin of the Putyvl’ line from Prince Fyodor Ivanovich is quite reliable,
and Wolf, claiming that the compiler of the pedigree confused Princes Fyodor Ivanovich
and Fyodor Semenovich (from the Smolensk line), made a serious mistake.
In modern historiography, there are opinions that the princes Borovskies (M. Bychkova)
and Domonts (N. Yakovenko) were branches of the Glynskys. In fact, this is not the case: the
Borovskies (Lithuanian), most likely, were the descendants of the princes Berdyabakovich, and
the Domonts were probably the branch of the princes Drutsk-Gorsky.
Prince Bogdan Fedorovich Glynsky in 1493 is mentioned as the first known leader of the
Dnieper (Cherkass) Cossacks. The highest career achievements of the princes Glynsky before
1500 were associated with the Siver land. Here, individual members of the clan occupied the
posts of the governors of Starodub, Chernigov and Putyvl’.